IBN KHALDUN'S CONSIDERATIONS RELATING TO ISLAMIC EDUCATION AND THEIR PERSPECTIVE ON THE FUTURE - Mohammad Al Farabi (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2022)
Ibn Khaldun is a thinker in Islamic education who is concerned with the circumstances of students' growth and development from the psychological, pedagogical, social, and spiritual perspectives. The purpose of this article is to look at Ibn Khaldun's social background, his main points of view on education, an analysis of those views, and projections of those views into the future. This study describes Ibn Khaldun's ideas on Islamic education in a descriptive manner using the library research method. Ibn Khaldun's ideas, which view learning potential as a natural thing that can be developed by choosing the right method of learning, are included in the findings found in this article. In this situation, educators can use the malakah and at-tadrij methods in accordance with the level of the students' cognitive development and their level of openness to learning. The ideas put forth by Ibn Khaldun can be developed as potential directions for Islamic education in the future, and his thoughts are pertinent to the current understanding of modern education. Ibn Khaldun's educational idea is regarded as a strong foundation for organizing Islamic education because it offers a strong foundation on the psychological, pedagogical, social, and spiritual aspects of Islam.